2012
DOI: 10.1021/la301090t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amphiphile Topology on the Aggregation of Oligocholates in Lipid Membranes: Macrocyclic versus Linear Amphiphiles

Abstract: A macrocyclic and a linear trimer of a facially amphiphilic cholate building block were labeled with a fluorescent dansyl group. The environmentally sensitive fluorophore enabled the aggregation of the two oligocholates in lipid membranes to be studied by fluorescence spectroscopy. Concentration-dependent emission wavelength and intensity revealed a higher concentration of water for the cyclic compound. Both compounds were shown by the red-edge excitation shift (REES) to be located near the membrane/water inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Filling the interior of CT with lipid chains, however, does not seem favorable from an energetic point of view. An alternative possibility, which is more consistent with the previous fluorescent data, 32 is that water molecules may be present in the interior of the macrocycle in the DLPC bilayer but may not form a continuous conduit to the membrane surface. In comparison to a TM channel with rapidly exchanging water molecules with the surface water, the CT molecules in DLPC bilayers under such a circumstance would experience much fewer water molecules in a given period of time, causing water cross peaks to develop more slowly.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Filling the interior of CT with lipid chains, however, does not seem favorable from an energetic point of view. An alternative possibility, which is more consistent with the previous fluorescent data, 32 is that water molecules may be present in the interior of the macrocycle in the DLPC bilayer but may not form a continuous conduit to the membrane surface. In comparison to a TM channel with rapidly exchanging water molecules with the surface water, the CT molecules in DLPC bilayers under such a circumstance would experience much fewer water molecules in a given period of time, causing water cross peaks to develop more slowly.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…Fluorescent data suggested that the linear trimer had a stronger preference for the membrane surface than the cyclic analogue. 32 Even though the linear trimer can aggregate intermolecularly at high concentrations and migrate into the hydrophobic core of the membrane, the aggregates seem to be quite unstable and in rapid equilibrium with the surface-bound species, which are expected to be quite mobile. The dynamics of LT observed in the 13 C− 1 H dipolar coupling data is consistent with its surface binding.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In colloid and materials research, self‐assembly of amphiphilic copolymer in solution is always a key focus . Even the simplest class of amphiphiles, the head or tail surfactants, at a specific and narrow concentration range of amphiphile in solution, named the critical micelle concentration, can form a wide variety of self‐assembled colloidal‐sized particles termed micelles depending on their relative volumes of the hydrophilic and hydrophobic components . For the formation of micelles, the hydrophilic portion of the amphiphile from solution minimizing unfavorable interactions between the surrounding organic solvent molecules and the hydrophilic groups of the amphiphile is effectively removed .…”
Section: Introductionmentioning
confidence: 99%